A new Amazonian species, description of male of Isanopus sahlbergi Bernhauer, 1917, and a revised key to species of Isanopus Sharp, 1876 (Coleoptera: Staphylinidae) - Klemann-Junior, Louri; Chatzimanolis, Stylianos (Zootaxa, 2025)
We describe the male of Isanopus sahlbergi, and a new species of the genus Isanopus from French Guiana, Isanopus itoupe Klemann-Junior & Chatzimanolis, sp. nov. We illustrate major diagnostic features and present a revised key to species of Isanopus.